Angiotensin-(1–7) protects from brain damage induced by shiga toxin 2-producing enterohemorrhagic Escherichia coli - Goldstein Raij, Jorge (2016)
Shiga toxin 2 (Stx2)-producing enterohemorrhagic induced brain damage. Since a cerebroprotective action was reported for angiotensin (Ang)-(1–7), our aim was to investigate whether Ang-(1–7) protects from brain damage induced by Stx2-producing enterohemorrhagic Escherichia coli. The anterior hypothalamic area of adult male Wistar rats was injected with saline solution or Stx2 or Stx2 plus Ang-(1–7) or Stx2 plus Ang-(1–7) plus A779. Rats received a single injection of Stx2 at the beginning of the experiment, and Ang-(1–7), A779, or saline was administered daily in a single injection for 8 days. Cellular ultrastructural changes were analyzed by transmission electron microscopy. Stx2 induced neurodegeneration, axonal demyelination, alterations in synapse, and oligodendrocyte and astrocyte damage, accompanied by edema. Ang-(1–7) prevented neuronal damage triggered by the toxin in 55.6 ± 9.5% of the neurons and the Stx2-induced synapse dysfunction was reversed. In addition, Ang-(1–7) blocked Stx2-induced demyelination in 92 ± 4% of the axons. Oligodendrocyte damage caused by Stx2 was prevented by Ang-(1–7) but astrocytes were only partially protected by the peptide (38 ± 5% of astrocytes were preserved). Ang-(1–7) treatment resulted in 50% reduction in the number of activated microglial cells induced by Stx2, suggesting an anti-inflammatory action. All these beneficial effects elicited by Ang-(1–7) were blocked by the Mas receptor antagonist and thus it was concluded that Ang-(1–7) protects mainly neurons and oligodendrocytes, and partially astrocytes, in the central nervous system through Mas receptor stimulation.